Penggunaan Alat Peraga Gelas Plastik Dan Kelereng Terhadap Tingkat Pemahaman Matematika Anak Usia Dini - Abdussalam Abdussalam; Zainuddin Zainuddin (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
The purpose of this study was to determine the effect of plastic cups & marbles props on the level of understanding, activity and understanding and activities of students in learning mathematics. This study uses a quantitative research method with a Quasi Experimental Design research design. The population in this study were all students of SD Negeri Mlajah 2 Bangkalan as many as 454 students, the samples were class IIa and class IIb, the determination of the sample was carried out using purposive sampling. The results showed that 1) there was an effect of plastic cups & marbles props on the level of students' understanding of mathematics learning and obtained a sig value. of 0.012 < 0.05 for class A and 0.004 < 0.05 for class B. 2) There is an effect of teaching aids plastic cups & marbles on student activities in class A mathematics learning with a value of sig. of 0.000 < 0.05. 3) there is no effect of plastic cups & marbles props on student activities in class B mathematics learning with a sig. of 0.986 > 0.05 in accordance with the criteria for the Multivariate Analysis of Variance test.